(3UhQ OQL Gdadc hCMcGegGs - (3OHTdje GdgfOj , OQhfjhS GdGScfOQGfjs ((3GdfLa s)
(3ChdgG (B:s
(3HYO aEf GdHQhL GdCKfi YTQ dcd HQL KdGKhf OQLI jSJOd HgG Ydi GdehGdjO s
(3BNQgG (B:s
(3cW(B: (3jbGQH GdehJi , jchf eSbGeG cg jbGQf VjdkG jchf TQjakG Je GdcJGH s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3fbdJ ef fSNI cJHJ SfI (B581s
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs